Legal Reasoning Hakim Dalam Proses Menetapkan Asal Usul Anak Dari Perkawinan Siri Di Pengadilan Agama Gorontalo - Yusuf, Asriwati I; Kasim, Nur Mohamad; Kamba, Sri Nanang Meiske (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Abstract The purpose of this research is to examine the legal reasoning by judges in determining the legitimacy of a child's origin from a clandestine marriage. This study employs empirical legal research with a qualitative research approach. The research findings indicate that in performing legal reasoning, judges must carefully make decisions regarding the status of a child for the best interests of the child. This process involves legal and social considerations, and requires the examination of evidence, petitioner's arguments, and relevant legal foundations with three main factors: evidence, witness testimonies, and legal provisions. When deciding cases of determining a child's origin and legal status, judges rely on the trial facts and evidence presented by the petitioners and assess whether the petitioner's marriage complies with Islamic law and Law Number 1 of 1974 on Marriage. The judges adhere to legal principles and concrete evidence in the decision-making process.